Strategi Pemasaran Destinasi Wisata Arung Jeram Ranau Desa Rantau Nipis Kec. Banding Agung Oku Selatan - Afta Apriansyah; Desy Misnawati; Ratu Mutialela Caropeboka (MUKASI: Jurnal Ilmu Komunikasi, 2022)
This study aimsto determine the Marketing Strategy of White Water Rafting Destinations in Rantau Nipis Village. Themethodused in thisstudyis a qualitative descriptive method, namely the process by selecting the object ofre search and then proceeding with the formulation of the problem and asking sever alquestion srelated to a study, then collecting data related to the formulation of the problem. Some of the techniquesused for data collection are observation, interviews, and documentation. The thing thatmust be done in marketing this white water rafting destination isto use a marketing strategy through social media by posting white water rafting activitieson social media.